The enhancement of intensive basic english students’ listening skill, group 3, of the Licenciatura en Idioma Inglés, Opción Enseñanza through the use of the bottom-up and top-down approaches using movie clips and radio station audios at the Western Multidisciplinary Campus of the University of El Salvador semester i-2019 - Álvarez Ramos, Dolores Saraí; García Fajardo, Fabiola Veraliz; Rodríguez Molina, Elsa María; Salazar García, Adriana Raquel (2024)
In this research study, researchers aimed to enhance IBE students´, group 3, listening skill through the use of bottom-up and top-down approaches using movie clips and radio station audios at the Western Multidisciplinary Campus of the University of El Salvador, semester I-2019 since the listening skill is the first skill students need to develop while learning a new language. So, researchers approached the field of study in order to identify and describe the problematic situation.